Verbal Language, Secondary Perception and the Emergence of Artistic Expression - Logan, Robert K. (New Explorations)

(untitled) (New Explorations Association, 2024)
A study is made of verbal language and artistic expression in human communication and their link to secondary perception, the way perception changed once humans achieved verbal language. The connection of verbal language to artistic expression through secondary perception is made as is the explosion of new tools, altruism, a theory of mind and religious practice, which are explored.